2016
DOI: 10.1002/jaba.308
|View full text |Cite
|
Sign up to set email alerts
|

A survey of publication practices of single‐case design researchers when treatments have small or large effects

Abstract: The published literature often underrepresents studies that do not find evidence for a treatment effect; this is often called publication bias. Literature reviews that fail to include such studies may overestimate the size of an effect. Only a few studies have examined publication bias in single-case design (SCD) research, but those studies suggest that publication bias may occur. This study surveyed SCD researchers about publication preferences in response to simulated SCD results that show a range of small t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
124
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 113 publications
(127 citation statements)
references
References 46 publications
3
124
0
Order By: Relevance
“…Cuijpers et al, 2016;Bai et al, 2020). However, these findings should be taken with caution because, although the metric of the d-statistic computed in this study is the same as in group designs, the effect sizes found in SCED studies are usually higher than those found in group designs such as randomized controlled trials (Parker and Vannest, 2009;Shadish et al, 2016). Overall, this study indicates that RNT-focused ACT protocols are promising for the treatment of depression and GAD and warrant conducting randomized controlled trials to compare their effect versus waiting-list control conditions or brief versions of empirically established treatments such as behavioral activation or cognitive therapy.…”
Section: Discussionmentioning
confidence: 77%
“…Cuijpers et al, 2016;Bai et al, 2020). However, these findings should be taken with caution because, although the metric of the d-statistic computed in this study is the same as in group designs, the effect sizes found in SCED studies are usually higher than those found in group designs such as randomized controlled trials (Parker and Vannest, 2009;Shadish et al, 2016). Overall, this study indicates that RNT-focused ACT protocols are promising for the treatment of depression and GAD and warrant conducting randomized controlled trials to compare their effect versus waiting-list control conditions or brief versions of empirically established treatments such as behavioral activation or cognitive therapy.…”
Section: Discussionmentioning
confidence: 77%
“…The authors did not report 5‐s acceptance which is typically the behavior researchers attempt to increase, thus the child may have never willingly opened the mouth. Finally, as with many single‐subject studies in this field, past reports have relied exclusively on retrospective collections of patients who received a similar treatment, raising important questions regarding the file drawer phenomenon (i.e., authors select studies with clear experimental effects to submit for publication and refrain from submitting work with insignificant effects, resulting in readers finding underrepresented negative results in the literature) as it related to treatment effectiveness (Shadish, Zelinsky, Vevea, & Kratochwill, ).…”
mentioning
confidence: 99%
“…Publication bias and scarcity of studies with null findings also appear to exist in the single-case design (SCD) research base (Kittleman, Gion, Horner, Levin, & Kratochwill, 2018;Sham & Smith, 2014), which commonly informs policy and practice for students with EBD. In fact, Shadish, Zelinsky, Vevea, and Kratochwill (2016) found that a "non-trivial minority" (p. 656) of SCD researchers (4-15%, depending on the condition) reported they would drop one or two cases with small effect sizes before submitting a study for publication. Moreover, reviews of the special education literature suggest that direct replication studies are exceedingly rare (Makel et al, 2016), rendering many research findings unverified.…”
Section: What Is Open Science and Why Is It Important?mentioning
confidence: 99%
“…Preregistrations were designed primarily for group-research designs and are less commonly used for qualitative and SCD studies. As SCDs (a) are used to identify evidencebased practices for students with EBD (Kratochwill et al, 2012) and (b) appear to be subject to researcher bias (Shadish et al, 2016;Sham & Smith, 2014), preregistration may be relevant for SCD researchers as well. Some SCD researchers are beginning to preregister their studies, such as the preregistration by Sadler for an SCD study exploring the use of video self-modeling to reduce challenging behaviors in students with ASD (see https://www.sreereg.org/framework/pdf/index.php?id=1725).…”
Section: State Of the Practice And Examples In Ebd Researchmentioning
confidence: 99%